2020
DOI: 10.7150/thno.38060
|View full text |Cite
|
Sign up to set email alerts
|

A tumor suppressor enhancing module orchestrated by GATA4 denotes a therapeutic opportunity for GATA4 deficient HCC patients

Abstract: Rationale: Effective targeting therapies are limited in Hepatocellular carcinoma (HCC) clinic. Characterization of tumor suppressor genes (TSGs) and elucidation their signaling cascades could shed light on new strategies for developing targeting therapies for HCC.Methods: We checked genome-wide DNA copy number variation (CNV) of HCC samples, focusing on deleted genes for TSG candidates. Clinical data, in vitro and in vivo data were collected to validate the tumor suppressor functions.Results: Focal deletion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Furthermore, the Western results confirmed that ZNF24 expression reduced the protein levels of c-MYC, cJUN, and fra-1 (Figure 4F and Supplement Figure S1D). Previous studies by Lu et al have shown that the WNT signaling pathway is associated with tumor cell senescence (27). This was consistent with our b-galactosidase staining results that ZNF24 induced A549i and PC9i cell senescence (Figure 4G and Supplement Figure S1E).…”
Section: Znf24 Induces Nsclc Cell Senescence By Inhibiting Wnt Signal Pathwaysupporting
confidence: 93%
“…Furthermore, the Western results confirmed that ZNF24 expression reduced the protein levels of c-MYC, cJUN, and fra-1 (Figure 4F and Supplement Figure S1D). Previous studies by Lu et al have shown that the WNT signaling pathway is associated with tumor cell senescence (27). This was consistent with our b-galactosidase staining results that ZNF24 induced A549i and PC9i cell senescence (Figure 4G and Supplement Figure S1E).…”
Section: Znf24 Induces Nsclc Cell Senescence By Inhibiting Wnt Signal Pathwaysupporting
confidence: 93%
“…In order to find out the precise mechanisms related to the ZNF24induced aging of THCA cells.Lu et al reported that Wnt signaling pathway is related to tumor cells senescence (11). We dected the impact of ZNF24 on Wnt signaling pathway in BCPAPi cells, and the qPCR assay result showed that ZNF24 expression significantly downregulated target genes in the typical Wnt signal transduction pathway, such as CCND2, cJUN, C-MYC and AXIN2 (Figure 4A).…”
Section: Znf24 Inhibits the Wnt Signal Transduction Pathway Activation Within Bcpapi Cells By Competitively Binding B-cateninmentioning
confidence: 91%
“…This indicates that CTNNB1 may be closely related to the tumorigenesis of THCA. In addition, Lu et al have reported that GATA4 directly binds and inhibits the bcatenin activity in transcribing target genes involved in the classical Wnt pathway, which result in Hepatocellular carcinoma (HCC) cells senescence (11). We therefore hypothesize that b-catenin might also be related to THCA tumor cell senescence.…”
Section: Introductionmentioning
confidence: 88%
“…MYH11 positively regulated GSTM5, PTGIS, ENPP2, and P4HA3 ( 32 ). GATA4 inhibits tumour growth by affecting the assembly of tumour suppressor enhancement modules ( 33 ). Overexpression of GATA4 can protect human granulosa cell tumours from apoptosis induced by TRAIL in vitro ( 34 ).…”
Section: Discussionmentioning
confidence: 99%